Evaluation of Reclamation Activities on Post-Mining Land - Gunawan Gunawan; Muhammad Chaerul; Natsar Desi; Erniati Erniati; A. Yusuf Harun; Eris Nur Dirman (Journal La Lifesci, 2026)
This study aims to evaluate reclamation activities on the post-mining land of PT Bumi Sentosa Jaya in Boedingi Village, Lasolo District, North Konawe Regency, Southeast Sulawesi Province. Mining activities carried out in the area have caused environmental degradation, particularly in soil quality and vegetation. Therefore, reclamation activities, including revegetation, need to be carried out to restore the ecological function of the land. This study uses the Normalized Difference Vegetation Index (NDVI) analysis method to evaluate the success rate of revegetation as an indicator of vegetation health and density. In addition, an analysis was conducted on the reclamation plan and the estimated costs required. The data used in this study consisted of Sentinel-2 satellite images and drone photos to obtain an accurate picture of topographical changes and vegetation growth. The results showed that the reclamation activities carried out by PT Bumi Sentosa Jaya succeeded in increasing vegetation density in the reclaimed area. The area of land that has been reclaimed reached 11.90 ha in the period from 2023 to 2024, with the success of revegetation measurable through an increase in NDVI values. The reclamation plan, which includes land preparation, planting of cover crops and pioneer plants, and plant maintenance, has been implemented in accordance with established standards. This study is expected to contribute to the development of reclamation and revegetation techniques in mining areas, as well as provide recommendations for companies and policy makers to improve the success of future reclamation activities.